Dimensionality and reliability of a screening instrument for students at-risk of dropping out from Higher Education. (March 2021) - Casanova, Joana R.; Gomes, Cristiano Mauro Assis; Bernardo, Ana B.; Núñez, José Carlos; Almeida, Leandro S.
Highlights: Dropout stems from a complex, gradual process of decision-making. Democratizing access and not democratizing the conditions success is a social fallacy. Early identification of at-risk students with quick and large-scale instruments. Screening instrument for students at risk of dropping out of Higher Education. Abstract: Dropout stems from a complex, gradual process of decision-making in which the demands and benefits of university attendance are weighed. Early identification of at-risk students benefits from quick and large-scale screening instruments. This study presents the dimensionality of a screening instrument for students at risk of dropping out of Higher Education, integrating three scales: Academic Exhaustion, Satisfaction with Education and Dropout Intention. A sample of 611 first-year university students was considered in the statistical analysis. The results demonstrate evidence of internal and external validity as well as the reliability of the screening instrument scores. The differences in correlation coefficients between these three scales and the students' intentions of completing the course and completing their education at their university, evaluated at two different points during the first semester, suggest that dropout analysis requires collecting information throughout the process of adjustment to higher education.